Functional significance of active site residues in the enzymatic component of the Clostridium difficile binary toxin - Davies, Abigail H. (Biochem Biophys Rep, 2016)
Clostridium difficile binary toxin (CDT) is an ADP-ribosyltransferase which is linked to enhanced pathogenesis of C. difficile strains. CDT has dual function: domain a (CDTa) catalyses the ADP-ribosylation of actin (enzymatic component), whereas domain b (CDTb) transports CDTa into the cytosol (transport component). Understanding the molecular mechanism of CDT is necessary to assess its role in C. difficile infection. Identifying amino acids that are essential to CDTa function may aid drug inhibitor design to control the severity of C. difficile infections. Here we report mutations of key catalytic residues within CDTa and their effect on CDT cytotoxicity. Rather than an all-or-nothing response, activity of CDTa mutants vary with the type of amino acid substitution; S345A retains cytotoxicity whereas S345Y was sufficient to render CDT non-cytotoxic. Thus CDTa cytotoxicity levels are directly linked to ADP-ribosyltransferase activity.